2016
DOI: 10.1016/j.bbr.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen facilitates and the kappa and mu opioid receptors mediate antinociception produced by intrathecal (−)-pentazocine in female rats

Abstract: Pentazocine, a mixed-action kappa opioid receptor (KOR) agonist, has high affinity for both KOR and the mu opioid receptor (MOR), and has been shown clinically to alleviate pain with a pronounced effect in women. However, whether local application of pentazocine in the spinal cord produces antinociception and the contribution of spinal KOR and MOR in mediating the effect of pentazocine in female rats remain unknown. Also, it is not known whether pentazocine-induced antinociception in females is estrogen-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Considering that LS represents a silent state of pain vulnerability, we speculate that failure of KOR signaling could determine the greater predisposition of females to develop persistent postsurgical pain. Further studies are needed to determine the contribution of hormonal (Lawson et al, 2010;Robinson et al, 2016;Sternberg et al, 2004), neurochemical, and genetic (Fillingim and Gear, 2004;Mogil et al, 2003;Rasakham and Liu-Chen, 2011)…”
Section: Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that LS represents a silent state of pain vulnerability, we speculate that failure of KOR signaling could determine the greater predisposition of females to develop persistent postsurgical pain. Further studies are needed to determine the contribution of hormonal (Lawson et al, 2010;Robinson et al, 2016;Sternberg et al, 2004), neurochemical, and genetic (Fillingim and Gear, 2004;Mogil et al, 2003;Rasakham and Liu-Chen, 2011)…”
Section: Mmentioning
confidence: 99%
“…Numerous studies report sex differences in the ability of exogenous KOR ligands to modulate pain in both rodents (Auh and Ro, 2012;Lomas et al, 2007;Mogil et al, Robinson et al, 2016;Sternberg et al, 2004;Terner et al, 2003a) and humans (Gear et al, 1996a;Gear et al, 1996bGear et al, , 1999Pande et al, 1996b). However, questions of sex differences in endogenous opioid receptor analgesia have not been rigorously studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the RVM, morphine and endogenous opioid peptides produce analgesia primarily via activating the μ‐type opioid receptor (MOR) and phosphorylation of MOR (pMOR) has been implicated in morphine tolerance, that is, decrease in MOR‐mediated analgesia. As previous studies suggested that estrogens may affect MOR signaling, we therefore explored whether aromatase inhibitors abrogated CPM‐induced colorectal hyperalgesia via affecting MOR phosphorylation. Figure A compares the relative level of pMOR in the RVM in saline‐treated, CPM‐treated, CPM + vehicle and CPM + FAD groups.…”
Section: Resultsmentioning
confidence: 99%
“…GPER (GPR30) co-localise with other pharmacologic classes of G α protein ligands, modulating serotonin and neuronal acetylcholine receptors (Xu et al 2009;Hammond et al 2011). Estrogen also modulates the strength of antinociception provided by opioid receptor agonists (Robinson et al 2016). The estrogen templates 6b, 6f, 6g, 6h and 6j use fitting points common to ligands acting at acetylcholine, serotonin and opiate receptors (Williams 2018).…”
Section: Gper Receptor Ligandsmentioning
confidence: 99%